Les principes généraux du droit français de la fonction publique - Timsit, Gérard (Les Cahiers de droit, 1978)
In France, public service rests upon the fundamental rule of the specialization of the law applicable to public servants. This entails that public servants are given a special status that singles them out from others in the other economic or social sectors. That special legal status of the French public service is however being diminished under the influence of external factors. Economic factors tend to subject public servants to the general law of labour contracts. Political factors tend to give public servants the complete enjoyment of fundamental rights and civil liberties. Finally, administrative factors such as policies favouring mobility and promotion tend to lessen the importance of rigid classification and grading. On the eve of major statutory changes in the law of the public service in Québec, Professor Timsit’s study provides an interesting comparative viewpoint.